Antibacterial Effectiveness of Mackerel (Rastrelliger sp) Fish Oil Emulgel against Staphylococcus aureus Bacteria using Well-Diffusion Method - Isnandar; Hendry Rusdy; Olivia Avriyanti Hanafiah; Yulita Olivia Saragih (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2025)
Introduction: The oral cavity is one of the entry points for a wide variety of bacteria. Most of these bacterial species are normal flora. These bacteria can turn into pathogens in poor oral health. One of the common normal flora bacteria that cause infections in the oral cavity is Staphylococcus aureus. Purpose: To determine the effectiveness of mackerel oil emulgel (Rastrelliger sp) in inhibiting Staphylococcus aureus bacteria. Methods: This research is an experimental study with a Post Test Control Design, with the well-diffusion method. The research sample used mackerel oil emulgel with various concentrations (10%, 5%, 2.5%, 1.25%, 0.62%, and 0.31%), Clinium® as positive control, and gel base as negative control. Results: The study showed that mackerel fish oil emulgel has effectiveness in inhibiting Staphylococcus aureus bacteria with the resulting inhibition diameter of 10% (16.95 mm), 5% (14.73), 2.5% (9.97 mm), 1.25% (8.01 mm), 0.62% (6.71 mm), and 0.31% (6.10 mm). Conclusion: Mackerel (Rastrelliger sp) oil emulgel has an antibacterial effect against Staphylococcus aureus bacteria.